Nahdlatul Ulama Sebagai Civil Society di Indonesia - Tjahyo Rawinarno Tjahyo Rawinarno (NIAGARA Scientific Journal, 2016)
As a western value, the concept of Civil Society has similarities with Islamic societal values. Many studies have found the reality that the society built by the Prophet Muhammad was egalitarian, participatory and had equality before the law. As a name, Civil Society can be said to be the idealized form of Western society, but its value bears many resemblance to the society governed by Islam. Nahdatul Ulama (NU) as the largest religious organization in Indonesia in its activities has played a role as a national civil society in spreading democratic values ​​within Islamic boarding schools or in terms of community advocacy, especially women, although this role still has several notes in it. Nahdatul Ulama's closeness to one of the national political parties makes it a political institution which creates limitations in embracing or being used as a forum for people who have different political choices.